The Dynamics Of Trust Among Medical Faculty Students At University X Toward The Government In The Issue Of The '6000 Foreign Doctors' Hoax - Adhin Ramadhan Khayatullah; Imanuel Deny Krisna Aji (CV. Ulil Albab Corp, 2025)
This study investigates the influence of hoax news about foreign doctors on the trust of University X medical students in the government. It focuses on two controversial events: the viral spread of claims regarding the government’s plan to recruit 6,000 foreign doctors and the dismissal of Faculty Dean. Both events were widely circulated on digital media, often with sensationalized and misleading headlines, fueling public confusion and skepticism, particularly within the academic medical community. Utilizing a descriptive quantitative approach, the research surveyed 277 out of 903 active students through convenience sampling. Data were gathered via an online questionnaire measuring both the extent of hoax news exposure and the students’ level of trust in government institutions. A simple linear regression analysis revealed a strong and significant relationship between hoax exposure and trust levels, with an R² value of 0.870 and a correlation coefficient of 0.933. This suggests that 87% of the variation in trust is attributable to the influence of hoax content. Despite students’ general awareness of current events, misleading narratives and delayed government responses significantly shaped their perceptions. The findings highlight the need for improved government crisis communication that is timely, transparent, and evidence-based. Additionally, it underscores the importance of fostering digital literacy and critical thinking in educational settings to help students critically assess information and maintain trust in public institutions, especially in health-related matters